ANALISIS AKUNTABILITAS PENGELOLAAN WAQAF PADA BAITUL MAL PROVINSI ACEH - Rizka Maulida; Ridwan Ridwan (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
Accountability of management of waqf is not in accordance with Act No. 41 of 2004 on Baitul Mal of Aceh province, due to the lack of socialization of Law and Accountability management of waqf has not been complied with by Act No. 41 of 2004 on Baitul Mal Province Aceh, because its implementation does not refer to the Law, Accountability waqaf management yet to be implemented and carried out activities in accordance with legislation and qanuns waqf, which is caused due to lack of training or development provided by the organization to improve the reliability of waqf manager. Pewaqaf did not pay attention and consider the ability nazir, so as to manage the waqf property is not optimal due to the lack of socialization of Law Number 41 Year 2004 on Waqf and Aceh Qanun No. 10 of 2007 on BaitulMal.